2018
DOI: 10.1016/j.jtcme.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

A technology developed from concept of acupuncture and meridian system, the clinical effect of BIOCERAMIC resonance on psychological related sleep disturbance with findings on questionnaire, EEG and fMRI

Abstract: Under the concept of meridian channels that belongs to traditional Chinese medicine, BIOCERAMIC Resonance (BR) has already been applied to many clinical medical research projects with functions mimicking of traditional acupuncture. Forty-five patients were recruited with chronic sleep disorders; 36 patients were given, applied to the device with BIOCERAMIC material and sound rhythm on chest skin surface; 9 patients were included as controls. All study participants completed a sleep pattern and quality of life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 43 publications
2
27
0
Order By: Relevance
“…1),8, 9, 10, 11, 12, 13, 14 one of the effects we observed was that the corresponding biological field can be transmitted via sound waves propagation. BIOCERAMIC Resonance is the technology of combining sound waves using specific frequency beats in conjunction with our proprietary BIOCERAMIC material which offers a new kind of clinical application of BIOCERAMIC technology 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14Fig.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…1),8, 9, 10, 11, 12, 13, 14 one of the effects we observed was that the corresponding biological field can be transmitted via sound waves propagation. BIOCERAMIC Resonance is the technology of combining sound waves using specific frequency beats in conjunction with our proprietary BIOCERAMIC material which offers a new kind of clinical application of BIOCERAMIC technology 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14Fig.…”
Section: Introductionmentioning
confidence: 75%
“…According to the experiment conducted by Wang et al., different harmonic frequencies of individual's original heartbeat produce coupled oscillation to different internal organs, which suggested a resonance pattern occurring between specific organs and vascular bed 11, 12, 13, 14. Wang also proposed that the function of resonance frequencies is to help blood enter the specific organs 11, 12, 13, 14.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 We have also studied the treatment of PLB with sound frequency (SF) on the specific meridian acupoints and found that there were a high percentage of subjects (91.7%) with increased electroencephalography (EEG) potentials between 15-27Hz (beta-1 frequency band) and new application in the clinical problem of sleep disorders. 10 Meanwhile, there were alternative treatments for sleep disorder, e.g. transcranial direct current stimulation (tDCS) treatment had been shown to increase beta-band power 11 and transcranial magnetic stimulation (TMS) had been shown consistently evoked beta-band oscillations in the parietal cortex.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 We have also studied the treatment of PLB with sound frequency (SF) on the specific meridian acupoints and found that there were a high percentage of subjects (91.7%) with increased electroencephalography (EEG) potentials between 15-27Hz (beta-1 frequency band) and new application in the clinical problem of sleep disorders. 10 Meanwhile, there were alternative treatments for sleep disorder, e.g. transcranial direct current stimulation (tDCS) treatment had been shown to increase beta-band power 11 and transcranial magnetic stimulation (TMS) had been shown consistently evoked beta-band oscillations in the parietal cortex.…”
Section: Introductionmentioning
confidence: 99%